The Role of Field Officers of Family Planning (FOFP) in The Unmet-Need Incidents on The Productive Age Couples - Kadek Widiantari; Made Pradnyawati Chania (Universitas Muhammadiyah Semarang, 2022)
The Family Planning Program is a program designed by the government in order to control the rate of population and birth rates, it aims to prosper the family and improve the quality of Indonesian generations in the future. The existence of Field Officers of Family Planning (FOFP) plays an important role in helping the government succeed in carrying out the family planning program, especially in reducing the number of unmet-need for family planning. The research objective is to obtain an in-depth picture of the role of the FOFP in the unmet-need for family planning in the North Denpasar District. This study uses a qualitative design with a single instrumental case study approach. The sample selection in this study used a purposive sampling technique with 10 informants and one key informant namely the Head of Population Control, Counseling and Movement in DP3A.P2KB in Denpasar. Interview results were analyzed using thematic analysis. The results of the study were five major themes namely the role of FOFP as: 1) Managing family planning programs, 2) Driving community participation 3) Family Empowerment and community participation, 4) Building and Developing Partnerships with various parties, and 5) obstacles and barriers.